Imagined Homelands in Print: AI-Based Text Segmentation and Register Analysis of the Finnish-American Press, 1876–1923. - Skantsi, Valtteri; Paju, Petri; Salmi, Hannu; Laippala, Veronika (Digital Humanities in the Nordic & Baltic Countries Publications (DHNB Publications), 2025)
This article presents a study on the use of artificial intelligence to analyze Finnish-language newspapers published in North America between 1876 and 1923. Using GPT-4 and LLaMA 3.1, we develop and evaluate a text segmentation method on large-scale digitized historical data, and we propose a hierarchical taxonomy for register (genre) classification based on manual annotation. We present a methodology for identifying text boundaries and, separately, a manually developed register taxonomy used to classify segments. Our analysis is grounded in a manually annotated stratified corpus of 500 documents selected from 312,300 digitized pages. Results demonstrate strong segmentation accuracy, contributing both to digital humanities methodology and the historical understanding of the Finnish-American immigrant press.